Development of a clinical prediction tool for extubation failure in pediatric cardiac intensive care unit - Saengsin, Kwannapas; Sittiwangkul, Rekwan; Borisuthipandit, Thirasak; Wongyikul, Pakpoom; Tanasombatkul, Krittai; Phanacharoensawad, Thanaporn; Moonsawat, Guanoon; Trongtrakul, Konlawij; Phinyo, Phichayut (Frontiers in Pediatrics, 2024)
Introduction/Objective: Extubation failure in pediatric patients with congenital or acquired heart diseases increases morbidity and mortality. This study aimed to develop a clinical risk score for predicting extubation failure to guide proper clinical decision-making and management.We conducted a retrospective study. This clinical prediction score was developed using data from the Pediatric Cardiac Intensive Care Unit (PCICU) of the Faculty of Medicine, Chiang Mai University, Thailand, from July 2016 to May 2022. Extubation failure was defined as the requirement for re-intubation within 48 hours after extubation. Multivariable logistic regression was used for modeling. The score was evaluated in terms of discrimination and calibration.Results: A total of 352 extubation events from 270 patients were documented. Among these, 40 events (11.36%) were extubation failure. Factors associated with extubation failure included history of pneumonia (OR 4.14, 95%CI 1.83-9.37, p=0.001), history of re-intubation (OR 5.99, 95% CI 2.12-16.98, p = 0.001), and high saturation in physiologic cyanosis (OR 5.94, 95% CI 1.87-18.84, p = 0.003). These three factors were utilized to develop the risk score. The score showed acceptable discrimination with an area under the curve (AUC) of 0.77 (95% CI 0.69-0.86), and good calibration.The derived Pediatric CMU Extubation Failure Prediction Score (Ped-CMU ExFPS) could satisfactorily predict extubation failure in pediatric cardiac patients. Employing this score could promote proper personalized care. We suggest conducting further external validation studies before considering implementation in practice.